1991
DOI: 10.1177/000494419103500304
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Power of Measured Interests in Tertiary Course Choice: The Case of Science

Abstract: The structural relations between measured interests, school subjects studied, and preference for science and technology type tertiary courses in a group of male independent school students were examined in a longitudinal study. Sources of data included the Career Assessment Inventory and tests of scholastic aptitude completed at the beginning of Year 10, details of school subjects studied in Years 11 and 12, final examination results (Year 12), and details of first preference for a university or college course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…A number of Australian studies (Ainley et al, 1994;Barnes, 1999;Kidd & Naylor, 1991) have reported links between students' decisions about science enrolment and their personality types. These studies were influenced by Holland's (1985) typology of personal interests, which have been described as Fpsychological traits which activate and arouse individuals to respond to external objects or events_ (Ainley et al, 1994, p. 127).…”
Section: Personality Typesmentioning
confidence: 99%
“…A number of Australian studies (Ainley et al, 1994;Barnes, 1999;Kidd & Naylor, 1991) have reported links between students' decisions about science enrolment and their personality types. These studies were influenced by Holland's (1985) typology of personal interests, which have been described as Fpsychological traits which activate and arouse individuals to respond to external objects or events_ (Ainley et al, 1994, p. 127).…”
Section: Personality Typesmentioning
confidence: 99%
“…The criteria were the 5 third-level clusters derived by Elsworth et al (1986). The study itself was complex, placing interests in contexts of aptitudes, subject choices and performances in the 2 final years of secondary school (Kidd & Naylor, 1991). Out of the mass of data and analyses used by Kidd (1992) I have chosen a synoptic view of the themes and criteria, which is shown in Figure 1.…”
Section: Table 4 a Typology Of Tertiary Course Choicementioning
confidence: 99%
“…More recent research and application, however, suggest that the Holland typology is not necessarily limited to aspects of the occupational world and may have more general implications. Naylor (1993), in arguing for a more general application of the typology, reviewed studies showing that it provided a comprehensive account of differences in school subject preferences (Care & Naylor, 1984;Naylor, 1989) and in choices of tertiary fields of study (Kidd & Naylor, 1991). These results suggest the possibility that Holland's typology as a theory of interests may be more general than its emphasis on occupations proposes.…”
mentioning
confidence: 99%